Evaluation of 90 Minute Healthy Napping as an Intervention to Improve Night Shift Nurses' Performance - Triwibowo, Cecep; Martina Siregar, Nurani; Elfina (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The night shift among nurses poses risks of circadian rhythm disruption, fatigue, and decreased alertness, which impact their performance. Napping during night shifts has been proposed as a strategy to reduce fatigue and enhance nurses' performance. Method: This study aims to analyze the effect of 90-minute healthy napping on the performance of night shift nurses at the Inpatient Installation of RSU Mitra Sejati Medan. This research employs a pre-experimental design with a one-group pretest-posttest approach. A total of 108 nurses participated in the study and were divided into two groups, each taking a 90-minute nap between 01:00–02:30 AM and 02:30–04:00 AM. Nurses’ performance was measured before and after the intervention using a questionnaire, and the data were analyzed using the Wilcoxon test. Result: The results indicate a significant improvement in nurses' performance following the intervention (p = 0.000). Before the intervention, the majority of nurses had a moderate performance level (60.2%), with only 11.1% exhibiting good performance. After the intervention, 61.1% of nurses improved to the good performance category. Conclusion: This study concludes that 90-minute healthy napping is effective in enhancing night shift nurses' performance. Implementing this strategy can serve as a solution to maintaining service quality during night shifts.